Wsparcie finansowe i rzeczowe działalności ochotniczych straży pożarnych przez gminę - Błażewski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Fire protection is the community’s own task. The community performs this task in cooperation with volunteer fire brigades. For this purpose, the community provides direct and indirect financing of acting of voluntary fire brigades. The provisions allows for a significant differentiation in the method of financing their activities.
Keywords: ochotnicza straż pożarna; społeczność; ochrona przeciwpożarowa; fundusze